PERAN MEDIA SOSIAL TERHADAP PENGEMBANGAN MEDIA PEMBELAJARAN INOVATIF DI ERA SOCIETY 5.0 - Early Ni’mah Hayati; Abdul Sukur; Alifian Nabila; Arum Dyan Kusuma; D. Adnindya Amalia; Farida Nur Aini; Yusuf Hanafi; Early Ni’mah Hayati; Abdul Sukur; Alifian Nabila; Arum Dyan Kusuma; D. Adnindya Amalia; Farida Nur Aini (Universitas Negeri Malang, 2024)
Technology plays a significant role, one of which is in the field of education. Currently, we are entering the era of society 5.0, which is defined as a concept of learning centered on humans and technology. In the context of education, teachers can integrate technology into learning activities, one of which is through the role of social media. Therefore, the aim of this article is to understand the role of social media in the development of innovative learning media in the era of society 5.0. This article utilizes the literature review method. Literature review method involves searching, exploring, reading, and examining relevant literature related to the research through accountable sources. The results of this research show that the use of social media such as TikTok and YouTube can be used as learning references and also as media in creative and innovative learning activities.